The Effect of Assertive Leadership on Teacher Innovation in Developing Environmentally Oriented Schools: an Ex Post Facto Study at Muhammadiyah Schools in Bogor - Suhardin Suhardin (Green Publisher Indonesia, 2026)
Schools are required to implement environmentally conscious awareness as a reference for the general public. This realization is greatly influenced by the leadership of the principal. This study aims to examine the effective leadership of the principal in providing space for teacher innovation in developing environmentally conscious schools. This study uses the expos facto method, in several Muhammadiyah schools in LEUWILIANG, LEUWISADENG, AND PAMIJAHAN Districts. In this study, it was found that assertive, effective principal leadership provides space for innovation for teachers to develop environmentally conscious schools compared to schools led by principals with a dominating leadership style. Thus, the researcher concluded that developing environmentally conscious schools requires assertive principal leadership, because the development of environmentally conscious schools greatly requires innovation from all parties within the school environment